Transformational leadership in nursing practice: challenges and strategies - Vanêska Brito Ferreira; Simone Coelho Amestoy; Gilberto Tadeu Reis da Silva; Letícia de Lima Trindade; Ises Adriana Reis dos Santos; Patrícia Alves Galhardo Varanda
ABSTRACT Objective: to understand the challenges and strategies adopted by nurses for the exercise of Transformational Leadership in a university hospital. Methods: qualitative and exploratory study, in which 25 nurses working in a university hospital in the state of Bahia, Brazil participated. Data collection took place through semi-structured interviews and categorized according to Thematic Analysis, using Nvivo software. Results: The prevalent challenges involved: lack of encouragement from the institution for the training of leaders; professional inexperience and young age; resistance to leadership and insubordination. The strategies adopted by nurses consist of acting as team examples and establishing dialogic relationships. Final considerations: The practice of Transformational Leadership has been relevant in the daily lives of nurses and contributes to the quality of care.